2020
DOI: 10.3389/fmars.2020.00662
|View full text |Cite
|
Sign up to set email alerts
|

Less Nutrients but More Phytoplankton: Long-Term Ecosystem Dynamics of the Southern North Sea

Abstract: We here assess long-term trends in marine primary producers in the southern North Sea (SNS) with respect to ongoing regional Earth system changes. We applied a coupled high-resolution (1.5-4.5 km) 3d-physical-biogeochemical regional Earth System model that includes an advanced phytoplankton growth model and benthic biogeochemistry to hindcast ecosystem dynamics in the period 1961-2012. We analyzed the simulation together with in situ observations. Coinciding with the decreasing nutrient level at the beginning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…This trend magnitude is comparable with the latest findings on chlorophyll-a historical trends in the North-West Shelf regions (0.4-0.96% year −1 ) Hammond et al (2020), noting that this estimate was considering offshore marine waters, not coastal zones. It is also comparable to Xu et al (2020) who found nearly 20-30% chlorophyll increase in the same study area between 1987 and 2012. Various numerical studies using climate models also project moderate increase in daily mean net primary production between 1980-1999 and 2080-2099 in the shallower southern North Sea (Holt et al, 2014(Holt et al, , 2016Pushpadas et al, 2015).…”
Section: Changes In Phytoplankton Bloom Dynamicssupporting
confidence: 89%
See 1 more Smart Citation
“…This trend magnitude is comparable with the latest findings on chlorophyll-a historical trends in the North-West Shelf regions (0.4-0.96% year −1 ) Hammond et al (2020), noting that this estimate was considering offshore marine waters, not coastal zones. It is also comparable to Xu et al (2020) who found nearly 20-30% chlorophyll increase in the same study area between 1987 and 2012. Various numerical studies using climate models also project moderate increase in daily mean net primary production between 1980-1999 and 2080-2099 in the shallower southern North Sea (Holt et al, 2014(Holt et al, , 2016Pushpadas et al, 2015).…”
Section: Changes In Phytoplankton Bloom Dynamicssupporting
confidence: 89%
“…Various numerical studies using climate models also project moderate increase in daily mean net primary production between 1980-1999 and 2080-2099 in the shallower southern North Sea (Holt et al, 2014(Holt et al, , 2016Pushpadas et al, 2015). We must emphasize that increasing chlorophyll concentration due to climate change is highly region specific (only occurring in some coastal areas) and very much debated (Xu et al, 2020). In fact, some studies only report shift in spring bloom timing and species composition, but not in magnitude.…”
Section: Changes In Phytoplankton Bloom Dynamicsmentioning
confidence: 95%
“…It is surrounded by heavily populated countries with important industrial and agricultural activities, resulting in large quantities of nutrients and pollutants being added to the North Sea through riverine inputs (Ducrotoy et al, 2000). As a result, the North Sea has suffered from eutrophication issues during several decades (e.g., Desmit et al, 2020;Xu et al, 2020;Friedland et al, 2021). Despite de-eutrophication policies implemented since the 1990s, such as the EU Marine Strategy Framework Directive (MSFD) which aims at reaching a Good Environmental Status (GES) in European waters, the North Sea still receives relatively high nutrient inputs (nitrogen and phosphorous, Van der Zande et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…This results in intense phytoplankton blooms occurring every year between March and October, with the southern parts of the North Sea, shallower and more affected by industrial and agricultural activities, presenting more intense blooms (Lancelot et al, 2005;Rousseau et al, 2013;Desmit et al, 2015Desmit et al, , 2020. Phytoplankton blooms are at the basis of the marine food web, driving biogeochemical cycles, producing oxygen and acting as a carbon pump (Xu et al, 2020). Phytoplankton spatial and temporal dynamics can be influenced by several factors, including the availability of nutrients and light, water temperature, and grazing (Capuzzo et al, 2017;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation